Statistika non parametrik: Analisis perbedaan pengunjung website resmi Kabupaten Malang menurut Devices Mobile menggunakan Uji Kruskal-Wallis - Anggraini, Eka Puspa (Maliki Interdisciplinary Journal, 2024)
Non-parametric statistical analysis using the Kruskal-Wallis test in this study to determine the existence of significant differences in two or more groups of research data samples. The data samples in this study are visitors to the official website of Malang Regency according to mobile devices in 2018, 2019, 2020 and 2021 which come from the book Malang Regency One Data Year 2022. The data samples were analyzed using descriptive statistical methods, Kolmogorov-Smirnov normality test and Kruskal-Wallis test. Descriptive statistical analysis resulted in different averages for 2018, 2019, 2020 and 2021, namely 6.857, 4.847, 1.545 and 2.018. Then the normality test with Kolmogorov-Smirnov found that the 2021 sample group was not normally distributed. Meanwhile, the Kruskal-Wallis test resulted in a significant difference in visitors to the official website of Malang district according to mobile devices in 2018, 2019, 2020 and 2021.